下顎歯肉に発生した乳頭状扁平上皮癌の1例 - 重岡, 学; 松本, 耕祐; 南川, 勉; 古森, 孝英; 長谷川, 巧実; 有本, 智美 (日本口腔外科学会雑誌, 2020)
Papillary squamous cell carcinoma (PSCC) is a rare variant of squamous cell carcinoma with only a few documented cases in the oral cavity. We report the case of a 70-year-old man who presented with papillary squamous cell carcinoma of the mandibular gingiva.　The patient was referred to our department because of a papillary tumor in the right mandibular gingiva. A physical examination revealed an exophytic papillary tumor in the right mandibular gingiva. Biopsy samples for histopathological diagnosis were taken two times. However, the biopsies did not reveal squamous cell carcinoma. Moreover, the pathological diagnosis obtained from intraoperative frozen-section analysis was cancer negative. Therefore, the operation consisted of resection of the tumor including a margin of 5-7 mm. Microscopically, the tumor showed exophytic papillary proliferation with fibrovascular cores and consisted of atypical squamous epithelial cells. The pathological diagnosis was PSCC. Three months later, local recurrence was observed and was resected again. The patient was healthy and remained free from tumors 18 months after the second operation. We report a rare case of PSCC. With small biopsy specimens, the diagnosis of PSCC was challenging.